Penerapan Elementor sebagai Perangkat Pengembangan Platform Pengawalan Rancangan Kerja PT. PVI - Irfan Ardiansah; Albert Triokto; Selly Harnesa Putri; Roni Kastaman; Totok Pujianto (JURNAL PERANGKAT LUNAK, 2023)
In the pursuit of optimizing information systems and website development for PT. PVI (Renstra), an extensive analysis was conducted on the use of CMS WordPress supplemented with the Elementor add-on as the primary tool for website construction. This analysis sought to assess the feasibility and capabilities of Elementor basic in meeting Renstra's requirements. Various critical aspects were evaluated, including account creation, login and logout systems, as well as form display and integration. Elementor basic, while providing the convenience of a user-friendly drag-and-drop design interface, falls short of fully satisfying Renstra's needs. A significant challenge encountered was Elementor basic's inability to create a seamless account creation system integrated with login and logout features. This posed a hindrance for website users seeking to input data, as they were unable to smoothly implement login functionalities within Elementor basic. To address these challenges, several recommendations are proposed. Firstly, Renstra should consider upgrading to Elementor Pro, which offers an array of comprehensive features, including streamlined form integration and efficient account creation. Secondly, designing an efficient login system within Elementor Pro to enable users to effortlessly create accounts, log in, and access their work progress is paramount. Thirdly, meticulous attention should be given to integrating form submission and the Progress Bar to enable users to submit data effortlessly and view their progress directly on the website, eliminating the need for manual Progress Bar adjustments. Fourthly, leveraging Elementor Pro's additional design features can significantly enhance the website's overall appearance, ensuring it aligns with user requirements. Finally, Renstra should explore the development of supplementary features to enrich the user experience, such as enhanced work progress management, progress notifications for registered users, or more restricted access for specific users. Implementing these recommendations will enable PT. PVI to enhance the efficiency and effectiveness of their information system and website. This, in turn, will enable them to provide superior services to their users, enhance transparency in progress reporting, and ultimately achieve their goal of optimizing their corporate information system.